Laparoscopy-assisted orchiopexy versus laparoscopic two-stage fowler stephens orchiopexy for nonpalpable testes: Comparative study - Alzahem, Abdulrahman (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND/PURPOSE: To assess the outcome of the primary laparoscopy-assisted orchiopexy (LAO) and the laparoscopic two-stage Fowler Stephens orchiopexy (FSO) for managing patients with nonpalpable testis in terms of safety, feasibility and efficacy. MATERIALS AND METHODS: This study included 94 patients (110 nonpalpable testes) who underwent laparoscopy at King Khalid University Hospital, Riyadh between July 1998 and June 2012. Patients were evaluated postoperatively to check the location and size of testes and to exclude any other complications. RESULTS: Mean age at presentation was 24+/−19 months (9-96 months). Orchiectomy was done for 5 atrophic testes. 36 open orchiopexy was done for 29 canalicular testes and 7 peeping testes. 35 LAO were done for 1 canalicular testis, 5 peeping testes, 16 low intraabdominal testes and 13 high intraabdominal testes. 34 FSO were done for 23 high intraabdominal testes, 9 low intraabdominal testes and 2 peeping testes. Median follow up was 12 months (1-84 months) and 6 patients were lost to follow up. The overall success rates for LAO and FSO were 88% and 63%, respectively. Overall testicular atrophy rates were 3% and 30% for LAO and FSO, respectively (OR 0.08 [95% CI, 0.01-0.69], P = 0.006). For high intraabdominal testes, the atrophy rates were 3% and 20% for LAO and FSO, respectively (OR 0.14 [95% CI, 0.02-1.21, P = 0.049).Testicular displacement rates were 9% and 7% for LAO and FSO, respectively (OR 1.5, 95% CI, 0.24-9.59, P = 0.514). CONCLUSIONS: Laparoscopy provides a safe and accurate modality for diagnosing and managing patients with nonpalpable testes. LAO appears to be feasible and effective in management of high intraabdominal testes. Further well-conducted comparative studies are needed.